SISTEM PENGENDALIAN BARANG DAGANG TOKO ANEKA KUE CIREBON - Herni Yanti; Agus Yudianto (BBM (Buletin Bisnis & Manajemen), 2020)
The development effort will lead to an ever increasing variety of problems, especially in its inventory. Inventories are assets of a very large company and prone to risk, whether the risk of damage or theft risk. In trading company's internal control over inventory is very important, the better the internal control over inventory the better inventory management in the business because inventory is the largest asset in the trading company.This research was conducted at Aneka Cake Shop Increased Noble, discussed in JL.Jagastru. Assorted Cake Shop is a pastry shop that sells a variety of products both dry and wet cake. The reason the author conducted research at Aneka Cake Shop is to evaluate the preparation of the internal control of goods is in conformity with the existing theory.In  this study,  the authors  conducted a  descriptive case  study.  The  method  of  data collection  is  by  interview,  observation,  and  documentation.  Source  of  data  used  is primary data. Then the authors made the analysis of degan using elements of internal control, whether it is in accordance with the existing theory. Based on the results it can be said that the internal controls Rising Star East Noble store for inventory is still weak. This can be seen from some of the elements of internal control that is not in accordance with the regulations and existing theories. The shortage lies in the structure of the organization still have a position and the lack of clear division of tasks. The documents were used.